To solve this system of equations, we can use the substitution method or the elimination method.
Using the first equation, x = 6y - 3, we can substitute this expression for x in the second equation.
2x + 7y = 13
2(6y - 3) + 7y = 13
12y - 6 + 7y = 13
19y - 6 = 13
19y = 19
y = 1
Now that we have found the value of y, we can substitute it back into the first equation to solve for x.
x = 6(1) - 3
x = 6 - 3
x = 3
Therefore, the solution to the system of equations is x = 3 and y = 1.
Solve the system of equations
x=6y-3
2x+7y=13
2 answers
Solve the system of equations.
8x-3y=-22
Y=10+4x
8x-3y=-22
Y=10+4x